2020
DOI: 10.1017/jie.2018.13
|View full text |Cite
|
Sign up to set email alerts
|

School House to Big House

Abstract: In 1991, the Australian Government released the Royal Commission into Aboriginal Deaths in Custody Report. Of the 339 recommendations, Recommendation 62 identified that there was an alarming over-representation of Indigenous youth in contact with the criminal justice system. The report called for immediate action by governments to develop strategies that would urgently reduce retention rates of Indigenous youth within the prison system. Analysis of the literature indicates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…This same research found that African American students are four times as likely and Latinx students twice as likely to be suspended or expelled for minor offences in primary school (Skiba et al, 2011). While the overrepresentation of Indigenous students in the use of exclusionary school discipline has also been observed in the Australian context, only a very small number of studies have investigated this to date (Beauchamp, 2012;de Plevitz, 2006;Gardiner et al, 1995;Graham et al, 2020a;O'Brien & Trudgett, 2020). None has been national, most have used only descriptive statistics or reviewed existing literature, and only one (Graham et al, 2020a) has conducted longitudinal or disaggregated analyses.…”
Section: Introductionmentioning
confidence: 95%
“…This same research found that African American students are four times as likely and Latinx students twice as likely to be suspended or expelled for minor offences in primary school (Skiba et al, 2011). While the overrepresentation of Indigenous students in the use of exclusionary school discipline has also been observed in the Australian context, only a very small number of studies have investigated this to date (Beauchamp, 2012;de Plevitz, 2006;Gardiner et al, 1995;Graham et al, 2020a;O'Brien & Trudgett, 2020). None has been national, most have used only descriptive statistics or reviewed existing literature, and only one (Graham et al, 2020a) has conducted longitudinal or disaggregated analyses.…”
Section: Introductionmentioning
confidence: 95%
“…O'Brien and Trudgett (2018) argue it is essential that Indigenous children are able to recognise their own culture within all systems of education. This requires more than scattering within the curriculum an occasional Indigenous song or an Indigenous story.…”
Section: Discussionmentioning
confidence: 99%
“…Federal, state and territory government policies that impose social and economic disadvantage must be addressed to achieve any significant change for the next generation of young First Nations peoples. First Nations peoples and organisations that facilitate First Nations led programs have better prospects than non-Indigenous government led programs at achieving long-term success (Hunt 2013;O'Brien and Trudgett 2018). Goldson (2006) stated that to institutionalise children with multifaceted needs and who present with complex vulnerabilities is a fundamentally violent act in of itself.…”
Section: Systemic Biasmentioning
confidence: 99%